Definite And Indefinite Nouns According to Al-Halawani - Shorish Jawhar Hamadamin; Abdulxalq Waly Fatah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This study is titled (Definite And Indefinite nouns according to Al-Halawani), and it is a research extracted from a master’s thesis, in which we follow up the efforts of Dr. Al-Halawani in studying the Definite And Indefinite nouns in his grammatical books, including his book (Annahu almuyassar) in particular, in order to reveal the aspects of accuracy and distinction in his handling of This topic, in addition to the aspects in which he may have failed, and the points of disagreement between him and other scholars, ancient and modern, and recording our observations in some of the places that were required. At the end of the research, we recorded the most important results that we reached in a concise and focused manner, then we put together a list of sources and references that we relied on in this work.